Enhancing Sustainable Management of Sibolangit Nature Tourism Park Through Comprehensive Stakeholder Analysis - Ginting, Theonesco B; OK Hasnanda Syahputra; Edwin Martin (Talenta Publisher, 2023)
The Sibolangit Nature Tourism Park (SNTP) holds immense potential as a natural attraction, but effective management faces challenges due to limited resource utilization and community engagement. To address this, a comprehensive stakeholder analysis was conducted. The research was conducted within SNTP, Deli Serdang Regency, between May and June 2021, utilizing questionnaires and in-depth interviews to gather primary data from 25 key informants. Stakeholders represented central and local governments, surrounding communities, and non-governmental organizations (NGOs) such as the Sibolangit Tourism Awareness Group. The collected data underwent thorough analysis to assess stakeholder interest and influence levels. Stakeholders were categorized into key players, context setters, and the crowd. Key players included the North Sumatra Natural Resources Conservation Center, SNTP, and the Deli Serdang Culture and Tourism Office, exerting significant influence in policy formulation and resource allocation. Context setters, represented by local communities, held substantial influence and played crucial roles in decision-making and implementation. The crowd, comprising NGOs, demonstrated high interest but lower influence in management. Collaboration among stakeholders, particularly central and local entities, emerged as pivotal for effective SNTP management. Stakeholders' roles significantly impacted management outcomes. This study highlights the necessity of holistic collaboration and balanced resource utilization for sustainable nature tourism management within SNTP. The findings contribute to a comprehensive understanding of stakeholder dynamics and their roles in achieving the objectives of SNTP management